Comparison of different timings of percutaneous coronary intervention in patients with transcatheter aortic valve implantation: a network meta-analysis - Qi Wen; Jiuyu Yang; Guomin Xu; Da'an Wang (Frontiers in Cardiovascular Medicine)
BackgroundThe combination of selective percutaneous coronary intervention (PCI) and transcatheter aortic valve implantation (TAVI) is a safe and feasible therapy and has become our preferred treatment option for patients with severe aortic stenosis and high-risk coronary heart disease. However, the timing of staged PCI is uncertain. The purpose of this meta-analysis is to compare the benefits and risks of TAVI alone, PCI before TAVI, simultaneous TAVI and PCI, and PCI after TAVI in TAVI patients, and to provide guidance for clinical decision-making on the timing of PCI in TAVI patients.MethodsWe searched Pubmed, Embase, the Cochrane Library and Web of Science as of April 2025. By employing Bayesian network meta-analysis, with the aid of R software (V4.3.2) and in combination with Stata (V15), the analysis included outcomes such as all-cause mortality, cardiovascular mortality, stroke, bleeding and myocardial infarction (MI). Pooled analysis was performed utilizing risk ratios (RR) and 95% confidence intervals (CI).ResultsA total of 13 studies involving 304,181 patients were included in the analysis. The research findings showed that the application of TAVI alone significantly reduced the all-cause mortality compared to PCI after TAVI (RR = 0.35, 95% CrI: 0.13, 0.88), and the lowest all-cause mortality rate was observed in the cumulative ranking (SUCRA = 75.89%). Compared with PCI after TAVI (RR = 0.57, 95% CrI: 0.41, 0.79) and TAVIplus PCI (RR = 0.72, 95% CrI: 0.54, 0.97), PCI before TAVI significantly reduced cardiovascular mortality and was found the lowest cardiovascular mortality in the cumulative ranking (SUCRA = 98.37%). In comparison to TAVIplus PCI (RR = 0.44, 95% CrI: 0.27, 0.71), PCI after TAVI significantly reduced the stroke rate and found the lowest stroke rate in the cumulative ranking (SUCRA = 97.21%). The application of TAVI alone significantly reduced the bleeding rate compared to TAVIplusPCI (RR = 0.61, 95% CrI: 0.60, 0.62), and the lowest bleeding rate was observed in the cumulative ranking (SUCRA = 88.14%). Compared with PCI before TAVI (RR = 0.12, 95% CrI: 0.04, 0.29) and TAVI (RR = 0.21, 95% CrI: 0.12, 0.34), TAVIplusPCI significantly reduced the incidence of myocardial infarction and was found the lowest incidence of myocardial infarction in the cumulative ranking (SUCRA = 96.44%).ConclusionThe timing of application of TAVI combined with PCI affects mortality and the incidence of cardiovascular events. Among them, PCI after TAVI may effectively reduce all-cause mortality, cardiovascular mortality, and stroke, but the interval between the two procedures remains uncertain. Future studies should investigate the optimal interval between PCI and TAVI to maximize clinical benefits. Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO.